Gaya Hidup dan Kemudahan Penggunaan terhadap Keputusan Penggunaan Dompet Elektronik Mahasiswa: Promosi sebagai Moderator - Trias Ajeng Miradayanti Putri; Arie Setyo Dwi Purnomo (Jurnal Kajian Ilmu Manajemen (JKIM), 2026)
This study examines the effects of lifestyle and perceived ease of use on students’ e-wallet usage decisions, with promotion as a moderating variable. The research aims to identify the factors influencing students’ decisions to adopt e-wallet services in digital financial transactions. This study employs a quantitative explanatory approach using a field research design. The population consists of active students of the Management Study Program at Universitas Trunodjoyo Madura, with a sample of 92 respondents determined using the Slovin formula. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS software. The results show that lifestyle and perceived ease of use have positive and significant effects on e-wallet usage decisions. Promotion significantly moderates the relationship between lifestyle and e-wallet usage decisions but does not moderate the relationship between perceived ease of use and e-wallet usage decisions. These findings imply that digital lifestyle and system convenience are key determinants in encouraging students to adopt e-wallet services, while promotional strategies can strengthen the influence of lifestyle in shaping digital payment behavior.